A Comprehensive Review: ICU Nursing Practices in Ventilator-Associated Pneumonia Prevention - Samira Essa Almaqadi, Zainah Qassim Al Shammari, Maryam Mohammed Masrahi, Fatimah Jabrel Jabari, Abdullalah Ahmed Bajahzar, Khalid Ahmed Alrashidi, Najla Mesfer Abdullah Al Fayi, Sanaa Mohammed Alshammari (Journal of International Crisis and Risk Communication Research, 2024)
Ventilator-associated pneumonia (VAP) remains a major challenge in intensive care units (ICUs), significantly increasing patient morbidity, length of hospital stay, and healthcare costs. VAP occurs 48–72 hours after intubation and is characterized by pulmonary infiltrates, systemic symptoms, and respiratory secretions. With a global prevalence ranging from 13.5% to 19.4%, effective prevention is essential. Intensive care nurses play a key role in implementing evidence-based practices such as hand hygiene, oral care, patient positioning, and ventilation management. However, gaps in knowledge, attitudes, and practice, along with diagnostic and resource constraints, hinder prevention efforts. This review examines the pathogenesis, microbiology, diagnostic challenges, and prevention strategies for VAP, highlighting the pivotal role of intensive care nurses. Recommendations include enhancing training, improving resource allocation, standardizing protocols, and establishing robust feedback mechanisms.